Development and validation of a specific scale on exercise compliance of lumbar disc herniation patients with conservative treatment - Gao, Caixiang; Huang, Xueyan; Han, Lu; Zhang, Jingying; Wang, Rui; He, Guijuan (Frontiers in Public Health, 2025)
BackgroundWe aim to develop a specific scale on exercise compliance of patients with lumbar disc herniation undergoing conservative treatment and to evaluate its reliability and validity.MethodsThe scale was developed in two stages. In the first stage, a preliminary version of the scale was developed through literature review, research group discussions, Delphi expert consultations, and pilot testing, based on the Health Belief Model and the concept framework of rehabilitation training compliance. In the second stage, the reliability and validity of the scale were tested among 430 patients with lumbar disc herniation undergoing conservative treatment who were discharged from the Massage Department of a tertiary hospital in Zhejiang Province within 2 months from May to August 2023. They were selected with a convenience sampling method.ResultsThe developed scale on exercise compliance included four dimensions: preparation compliance, exercise compliance, supervision compliance, and recommendation compliance, with a total of 20 items. The content validity index for the scale and each item was 0.914 and 0.813 to 1.000, respectively. An exploratory factor analysis extracted four common factors with a cumulative variance contribution rate of 73.578%. The results of confirmatory factor analysis showed a good model fit, with a chi-square/degree of freedom ratio of 2.642, incremental fit index of 0.929, comparative fit index of 0.928, and root mean square error of approximation of 0.069. The scale’s Cronbach’s α coefficient was 0.942, split-half reliability was 0.866, and test–retest reliability was 0.901.ConclusionThe development process of this exercise compliance scale was scientifically rigorous. The scale exhibits excellent reliability and validity, making it an effective tool for assessing exercise compliance in LDH patients receiving conservative treatment.